PERANAN BADAN USAHA MILIK DESA ( BUMDes ) DALAM PENINGKATAN EKONOMI MASYARAKAT ( STUDI PADA BUMDes DESA PEKAN TEBIH KECAMATAN KEPENUHAN HULU KABUPATEN ROKAN HULU ) - -, Samadi; Rahman, Arrafiqur; -, Afrizal (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This research aim to to know the Body Role of is Effort Countryside Property ( BUMDes) in Make-Up of Society Economics, specially society of consumer of fund BUMDes in Countryside of Week of Tebih of District of Fullness of Pate;Upstream of Sub-Province of Rokan Pate;Upstream. Research Population is some of consumer of fund of BUMDes of Countryside of Week of Tebih year 2013 counted 277 people and determination sampel use the method Proposional so that its sampel research amount to 42 people. In analysing research data use the descriptive method qualitative, only elaborating result from question interview the field moment